Urban design for social cohesion; housing for the displaced - Olvera Covarrubias, Karla Patricia (My University, 2025)
The year 2015 marked a cornerstone in Sweden’s history of hosting refugees, receiving 162,877 asylum applications. Although the number of applicants decreased to around 12,000 thanks to changes in migratory regulations, the future is unpredictable. The journey of the displaced implies external forces (e.g., weather disasters, war) that make it impossible for the person to stay in their place of origin. These individuals seek asylum in other nations, but it is a complex process involving legal, social, and cultural factors. Additionally, resistance from local populations poses a challenge to their establishment. The thesis aims to showcase the importance of housing as a key factor for the displaced’s integration on the city scale; as well as open the dialogue and reflect on the relationship between the built environment and a cohesive society. Following “Research by Design” methodology, case studies of Swedish reception units (e.g., SällBo) as well as other European models (e.g., Les Cinq Toits) were observed. The thesis extracts design guidelines addressing collective living, adaptable spaces, visual security, and other qualities that have good outcomes in their establishment. By placing the scenario of a speculative housing prototype in Gothenburg focused on the displaced family and individual as well as potential new residents and visitors, explorations of design were made with the purpose of merging conventional spatial rules for dwellings and local construction regulations with design guidelines tailored to their needs. The result is a series of replicable frameworks for designing dwellings that have a particular focus on the displaced’s recovery and belonging, demonstrating the role architects play in addressing fundamental global issues through prioritizing spaces for their well-being.
Keywords: Gothenburg; displaced; migration; housing planning; housing design; housing; integration; speculative design; well-beings